(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Foot is a complex, multi-segmented structure. Each segment act in a coordinated manner to provide support and absorb shock during locomotion. Foot morphology differs among population groups. The objectives of this study were to determine the selected foot dimensions and foot shape of adult Bangalee females to find out any ethnic characteristics of their own. Materials and methods: The study was conducted on 200 Bangalee adult females within 18-44 years age. Foot length and foot breadth were measured by slide caliper. Foot index was calculated from foot length and foot breadth. Foot shape was determined from foot index by using a pre determined formula. Results: The mean value for length, breadth and index of foot in Bangalee females were 22.91±0.79 cm, 8.55±0.4cm and 37.35±1.92 respectively. Most of the participants (68%) had standard foot shape. 17.5% women had slender foot whereas14% had broad foot shapes. Conclusion: The results of this study should be useful for anatomists, anthropologists and forensic experts. JCMCTA 2020 ; 31 (1) : 54-57